The Multiplier Concept and Monetary Restraint: A Response - Vernon, Jack (Quarterly Journal of Economics, 1976)
Journal Article The Multiplier Concept and Monetary Restraint: A Response Get access Jack Vernon Jack Vernon University of Florida Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 3, August 1976, Pages 518–520, https://doi.org/10.2307/1886051 Published: 01 August 1976